The Case for Telemedicine from a Sustainability Perspective - Elisa SALA; Luisa BROGONZOLI; Marco DE BENEDICTIS; Maria Franca TOMASSI; Gabriella PAOLI; Mauro GIACOMINI (Applied Medical Informatics)
This article examines telemedicine from a sustainability perspective, emphasising its alignment with the triple bottom line: social, environmental and economic benefits. Socially, telemedicine democratises healthcare by facilitating constant communication between patients and physicians, especially for the elderly, chronic patients and those with mobility difficulties. With regard to the environment, a life-cycle approach reveals the considerable potential of telemedicine to reduce greenhouse gas emissions by minimising patient travel. Furthermore, telemedicine also has the potential to decrease other environmental impacts, such as energy consumption in healthcare facilities and waste from personal protective equipment. From an economic perspective, telemedicine facilitates more efficient resource allocation, enhances system sustainability, and has thus the potential to reduce costs. It enables earlier and more optimal treatment of patients, improves adherence to treatment plans, and reduces hospitalisations and emergency room visits. The article examines the role of telemedicine in the transformation of the healthcare landscape, particularly in the context of Ministerial Decree 77 and the National Plan for Recovery and Resilience (PNRR), with a focus on the Liguria Region. The Liguria telemedicine plan, which was approved in 2023 and financed by the PNRR, has been designed to meet the health needs of an ageing population. The initial results indicate a growing adoption of telemedicine, particularly in the fields of endocrinology and diabetology. The discrepancies in data between sources signal the necessity for enhanced data integration.